Mechanisms of immunological tolerance in central nervous system inflammatory demyelination. Issue 3 (22nd March 2015) - Mari, Elisabeth R.; Moore, Jason N.; Zhang, Guang‐Xian; Rostami, Abdolmohamad
Abstract Multiple sclerosis is a complex autoimmune disease of the central nervous system that results in a disruption of the balance between pro‐inflammatory and anti‐inflammatory signals in the immune system. Given that central nervous system inflammation can be suppressed by various immunological tolerance mechanisms, immune tolerance has become a focus of research in the attempt to induce long‐lasting immune suppression of pathogenic T cells. Mechanisms underlying this tolerance induction include generation of regulatory T cell populations, anergy and the induction of tolerogenic antigen‐presenting cells. The intravenous administration of encephalitogenic peptides has been shown to suppress experimental autoimmune encephalomyelitis and induce tolerance by promoting the generation of regulatory T cells and inducing apoptosis of pathogenic T cells. Safe and effective methods of inducing long‐lasting immune tolerance are essential for the treatment of multiple sclerosis. By exploring tolerogenic mechanisms, new strategies can be devised to strengthen the regulatory, anti‐inflammatory cell populations thereby weakening the pathogenic, pro‐inflammatory cell responses.